3. The Karelian language in Finland : An Overview of a Language in Context - Sarhimaa, Anneli
During the initial stage of the research project ELDIA (European Language Diversity for All) in 2010, "structured context analyses" of each speaker community at issue were prepared. These context analyses will act as a starting point for further deepened research by linguists, sociologists and lawyers. Thus, they will form the basis of further case-specific reports and the comparative report which will be the main outcome of the whole project. However, as these will be available for interested readers only at the end of the project, we wanted to publish shorter versions summarising our work so far already at this stage, thus providing up-to-date information for both the academic community and stakeholder groups. This paper, based on the context analysis by Anneli Sarhimaa, gives a brief and up-to-date overview of the status of and research about the Karelian language in Finland. As all papers appearing in the series Working Papers in European Language Diversity, these context analyses have been subject to an anonymous peer-reviewing process. Whenever the present document is referred to, due reference to the author and the ELDIA project should be made. For more information about the ELDIA project see http://www.eldia-project.org/. As all papers appearing in the series Working Papers in European Language Diversity, these context analyses have been subject to an anonymous peer-reviewing process. Whenever the present document is referred to, due reference to the author and the ELDIA project should be made. For more information about the ELDIA project see http://www.eldia-project.org/.